Laju Aliran Massa Fluida Pada Karbon Aktif Bambu Betung Dengan Variasi Temperatur Karbonisasi 400, 500, 600, 700, 800 Dan Temperatur Aktivasi 600oC - Proverbs Sitanggang, Rekki; Wijaksana, Hendra; Priambadi, IGN. (Teknik Desain Mekanika, 2021)
Abstract Along with the times and the continued increase in population, there is an impact on social changes in people's lives, one of which is human comfort in activities. Indonesia is a tropical country so the use of air conditioning is very necessary, one of which is the Evaporative Air Cooler which uses the working principle of direct evaporative cooling, the cooling effect is given by the evaporation process of water that occurs in the wet pad material. The pad material in this direct evaporative cooling system is a cooling medium derived from local bamboo, namely bamboo betung. This study uses activated carbon charcoal as a pad material to determine the effect of the mass flow rate of the fluid on the direct evaporative cooling system. By using a carbonization temperature of 400, 500, 600, 700, 800 oC and then activated at a temperature of 600oC. The results of all tests show that the specimen that has been carbonized with a temperature of 500 oC and activation of 600oC or AKRB 500 has the highest mass flow rate characteristic of 13.6 x 10-8 kg/s which can be used as potential for the manufacture of new pad materials in the direct system. evaporative cooling Keywords: Direct evaporative cooling, bamboo betung, carbonization, activation, The mass flow rate of the fluid